Prediction of fatigue life of welded details in cable-stayed orthotropic steel deck bridges - Yan, Fei; Chen, Weizhen; Lin, Zhibin (Engineering structures, 2016)
•Predict fatigue life of welded details in cable-stayed orthotropic steel deck bridges.•Compute stress level at welded joints using a mixed-dimensional finite element method.•Sampling traffic information using Monte Carlo sampling approach. Welded details in cable-stayed orthotropic steel deck bridges are prone to fatigue damage and thus it is vital to fully understand their fatigue performance and effectively predict their fatigue life. In this study, fatigue life of welded joints is predicted based upon Miner’s damage rule and the histogram of stress range frequency with consideration of traffic data. Stress level and the influence surface at welded joints of interest are computed using a mixed-dimensional finite element method. To accurately evaluate the traffic effect on fatigue performance, Monte Carlo simulation is used to generate the vehicle-induced stress history at critical welded joints, in such a way to develop the stress range frequency histogram. The rain-flow counting algorithm is utilized to determine the stress cycles while fatigue damage is computed by formula of Miner’s rule. The proposed procedures for fatigue life prediction are implemented in a case study of a cable-stayed orthotropic steel deck bridge.